Analysis of Biology Teachers Problem in Integrating Islam with Biology Learning at Madrasah Aliyah - Ardi, Ardi; Ramadhani, Syifa Zalina; Rahmah, Erina Ainul (Journal Of Biology Education Research (JBER), 2026)
The integration of Islamic values into biology learning is an important aspect of science education in Madrasah Aliyah (MA), where teachers play a key role in linking scientific concepts with Islamic teachings. However, several previous studies have reported that biology teachers in MA still face various challenges in integrating Islamic values with biology learning. Therefore, this study aims to conduct a systematic literature review to identify and analyze the problems faced by teachers in integrating Islam and biology learning. This study employed the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method. A comprehensive literature search was conducted using the Google Scholar and DOAJ databases, focusing on publications from 2017 to 2025. The keywords used were (“Biology Teacher” OR “Science Teacher”) AND (“Challenge” OR “Problem”) AND (“Integration of Islam and Science” OR “Integration of Islam and Biology”) AND (“Madrasah” OR “Islamic School”) AND (“Islamic Value”) AND (“Biology Learning” OR “Biology Education”). From the initial identification of 153 articles, 20 articles met the predetermined inclusion criteria and were analyzed in depth using content analysis. The findings reveal that teachers generally encounter three main challenges: epistemological, pedagogical, and structural. Epistemological challenges relate to teachers’ understanding of the relationship between Islamic teachings and scientific concepts. Pedagogical challenges include difficulties in designing integrative learning strategies and developing appropriate teaching materials. Structural challenges involve limited training opportunities, inadequate learning resources, and curriculum constraints. This study contributes to the development of a conceptual framework for understanding the challenges faced by teachers in integrating Islam and science in biology education. It also provides recommendations for madrasahs to enhance professional teacher training, develop integrative curricula, and provide adequate teaching materials to support integrated learning.